Multinational corporations and their Human Rights violations: the quest for a legally binding treaty - Torr, Daniel (Department of Public Law, 2024)
The rise to power of multinational corporations (MNCs) during the era of globalisation has resulted in their establishment as formidable players in the international arena. In their pursuit for profit maximisation, MNCs tend to operate in the developing world where they are often involved or implicated in human rights violations. As the current corporate social responsibility (CSR) initiatives aimed at addressing global corporate abuses are non-binding on MNCs, the UN has initiated a treaty-drafting process with the aim to adopt a business and human rights (BHR) treaty. Once signed and ratified by States, this treaty will impose direct legally binding obligations on MNCs vis-à-vis universal human rights standards. This development has resulted in much controversy and disagreement amongst States, with predominantly industrialised States opposing this treaty's adoption. Consequently, the question is whether implementing a BHR treaty is justified. Providing an answer to this question requires a two-fold analysis. First, whether a BHR treaty is necessary in order to end the impunity of MNCs and second, whether adopting this treaty is politically feasible.